Ball milling and hot-melt extrusion of indomethacin-l-arginine-vinylpyrrolidone-vinyl acetate copolymer: Solid-state properties and dissolution performance - Iemtsev, Anton; Zemánková, Alžběta; Hassouna, Fatima; Mathers, Alex; Klajmon, Martin; Slámová, Michaela; Malinová, Lenka; Fulem, Michal (International journal of pharmaceutics, 2022)
Commonly applied approaches to enhance the dissolution properties of low water-soluble crystalline active pharmaceutical ingredients (APIs) include their amorphization by incorporation into a polymeric matrix and the formation of amorphous solid dispersions, or blending APIs with low-molecular-weight excipients and the formation of a co-amorphous system. This study focused on the preparation and characterization of binary (consisting of indomethacin (IND) and polymer - copovidone (PVP VA 64), as a carrier, or amino acid - L-arginine (ARG), as a co-former) and ternary (comprising the same API, polymer, and amino acid) formulations. Formulations were produced by ball milling (BM) and/or hot-melt extrusion (HME), and extensive physicochemical characterization was performed. Specifically, the physicochemical and solid-state properties of a model IND-ARG system incorporated into a polymeric matrix of PVP VA 64 by HME and BM as well as by combined BM/HME method together with the impact of the preparation strategy on the dissolution profiles and long-term physical stability were investigated. Ball-milled binary and ternary formulations were found to be amorphous. The residual crystals corresponding to IND-ARG salt were identified in the ternary formulations produced via HME. Despite the presence of a crystalline phase, dissolution tests showed that ternary systems prepared by HME exhibited improved IND solubility when compared to pure crystalline IND and their corresponding physical mixture. None of the binary and ternary formulations that were initially fully amorphous did undergo recrystallization during the entire period of preservation (minimum of 12 months) in dry conditions at 25 °C.
Keywords: arginin; indomethacin; vinylové sloučeniny; Arginine; polymery; Ternary formulation; Amorphous solid dispersion; rozpustnost; Polymers; Physical stability; Dissolution performance; Co-amorphous; Vinyl Compounds; Indomethacin; Solubility